2015
DOI: 10.3201/eid2107.150213
|View full text |Cite
|
Sign up to set email alerts
|

Slow Clearance ofPlasmodium falciparumin Severe Pediatric Malaria, Uganda, 2011–2013

Abstract: Plasmodium falciparum resistance to artemisinin derivatives is emerging in Asia. We examined molecular markers of resistance in 78 children in Uganda who had severe malaria and were treated with intravenous artesunate. We observed in the K13-propeller domain, A578S, a low-frequency (3/78), nonsynonymous, single-nucleotide polymorphism associated with prolonged parasite clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 14 publications
(30 reference statements)
9
52
1
Order By: Relevance
“…In Africa, highly diverse and low-frequent K13 mutant alleles have been observed, with no evidence of selection, and none of these were associated with clinical artemisinin resistance assessed by the presence of parasites on day 3 following artesunate monotherapy or a 3-d ACT course. It is thought that artemisinin resistance has not been established in Africa, supported by the additional absence of evidence of invasion by Asian K13 alleles validated as molecular marker of artemisinin resistance (C580Y, R539T, I543T, Y493H), confirming previous smaller-sized studies (Conrad et al 2014;Torrentino-Madamet et al 2014;Cooper et al 2015;Escobar et al 2015;Hawkes et al 2015;Isozumi et al 2015;Kamau et al 2015;Taylor et al 2015). Haplotyping studies on the most common African mutant 578A !…”
Section: -800 Nmsupporting
confidence: 78%
“…In Africa, highly diverse and low-frequent K13 mutant alleles have been observed, with no evidence of selection, and none of these were associated with clinical artemisinin resistance assessed by the presence of parasites on day 3 following artesunate monotherapy or a 3-d ACT course. It is thought that artemisinin resistance has not been established in Africa, supported by the additional absence of evidence of invasion by Asian K13 alleles validated as molecular marker of artemisinin resistance (C580Y, R539T, I543T, Y493H), confirming previous smaller-sized studies (Conrad et al 2014;Torrentino-Madamet et al 2014;Cooper et al 2015;Escobar et al 2015;Hawkes et al 2015;Isozumi et al 2015;Kamau et al 2015;Taylor et al 2015). Haplotyping studies on the most common African mutant 578A !…”
Section: -800 Nmsupporting
confidence: 78%
“…Of these, A569T was previously observed only in Kenya, where it was present in a single sample, as in our analysis (24). In contrast, the A578S polymorphism is present in Africa (8,(24)(25)(26)(27)(28) and Bangladesh (29). Conflicting findings have been reported regarding the role of A578S in artemisinin resistance (8,26,30).…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast, the A578S polymorphism is present in Africa (8,(24)(25)(26)(27)(28) and Bangladesh (29). Conflicting findings have been reported regarding the role of A578S in artemisinin resistance (8,26,30). Previous computational modeling using the betapropeller domain of the btbkelch protein krp1 (PDB ID 2WOZ) suggested that a structural change induced by the A578S mutation potentially disrupts the normal function of the Pfkelch13 protein (29).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The K189T variant is common in African isolates [38,39] and is not believed to cause increased clearance times following ACT. While the A578S variant has been associated with increased clearance times [40], this mutation was only observed in a small fraction of our strains. Additionally, strains possessing known resistance mutations in PfK13 are FSM susceptible (R. L. Edwards et al, unpublished data) suggesting that selection for artemisinin resistance does not result in FSM resistance.…”
Section: Genotyping Of Known Resistance Loci Does Not Reveal a Changementioning
confidence: 60%